Peanut Can Be Used as a Reference Allergen for Hazard Characterization in Food Allergen Risk Management: A Rapid Evidence Assessment and Meta-Analysis - Turner, Paul J. (2021)
Regional and national legislation mandates the disclosure of “priority” allergens when present as an ingredient in foods, but this does not extend to the unintended presence of allergens due to shared production facilities. This has resulted in a proliferation of precautionary allergen (“may contain”) labels (PAL) that are frequently ignored by food-allergic consumers. Attempts have been made to improve allergen risk management to better inform the use of PAL, but a lack of consensus has led to variety of regulatory approaches and nonuniformity in the use of PAL by food businesses. One potential solution would be to establish internationally agreed “reference doses,” below which no PAL would be needed. However, if reference doses are to be used to inform the need for PAL, then it is essential to characterize the hazard associated with these low-level exposures. For peanut, there are now published data relating to over 3000 double-blind, placebo-controlled challenges in allergic individuals, but a similar level of evidence is lacking for other priority allergens. We present the results of a rapid evidence assessment and meta-analysis for the risk of anaphylaxis to a low-level allergen exposure for priority allergens. On the basis of this analysis, we propose that peanut can and should be considered an exemplar allergen for the hazard characterization at a low-level allergen exposure. Resumen: La legislación regional y nacional exige la divulgación de alérgenos "prioritarios" cuando están presentes como ingrediente en los alimentos, pero esto no se extiende a la presencia involuntaria de alérgenos debido a instalaciones de producción compartidas. Esto ha dado lugar a una proliferación de etiquetas de precaución para alérgenos ("pueden contener") (PAL) que los consumidores alérgicos a los alimentos suelen ignorar. Se han hecho intentos para mejorar la gestión del riesgo de alérgenos para informar mejor el uso de PAL, pero la falta de consenso ha llevado a una variedad de enfoques regulatorios y a la falta de uniformidad en el uso de PAL por parte de las empresas alimentarias. Una posible solución sería establecer “dosis de referencia” acordadas internacionalmente, por debajo de las cuales no se necesitaría PAL. Sin embargo, si se van a utilizar dosis de referencia para informar la necesidad de PAL, entonces es esencial caracterizar el peligro asociado con estas exposiciones de bajo nivel. Para el maní, ahora hay datos publicados relacionados con más de 3000 desafíos doble ciego controlados por placebo en individuos alérgicos, pero falta un nivel similar de evidencia para otros alérgenos prioritarios. Presentamos los resultados de una evaluación rápida de la evidencia y un metanálisis del riesgo deanafilaxia a una exposición a alérgenos de bajo nivel para alérgenos prioritarios. Sobre la base de este análisis, proponemos que el cacahuete puede y debe considerarse un alérgeno ejemplar para la caracterización del peligro en una exposición a un alérgeno de bajo nivel.